Biomarkers in radiation oncology. (April 2008) - Russo, Andrea L; Citrin, Deborah; Camphausen, Kevin
The discovery of biomarkers in patients receiving radiation therapy for cancer is occurring at an exceptional pace. There are a number of ways to conduct biomarker investigations, although the majority of clinically relevant biomarker studies have used immunohistochemistry (IHC) on tissue specimens. Using IHC, expression of several pre-radiation biomarkers, such as VEGF, EGFR, YKL-40, murine double minute 2 and Rad51, has been associated with a poor outcome. Because tumor tissue may be difficult to obtain and IHC studies can be difficult to reproduce and standardize, investigators have attempted to find similar results when studying biomarkers of nontumor biospecimens, such as serum and urine. This has led to the discovery of a number of soluble biomarkers predictive of outcome (e.g., YKL-40, VEGF and matrix metallopeptidase-2). As we transition from the use of biopsy-based markers to surrogate soluble biomarkers in the hope of bringing these biomarkers into clinical use, we must ensure methods of standardization in sample collection, processing, storage and analysis to allow widespread reproducibility and accuracy of results.